Strategic Purchasing and Performance of Public Procurement in Rwanda - Euthyme, Mudaheranwa (International Journal of Scientific Research and Management (IJSRM), 2021)
The purpose of the study was to examine the relationship between strategic purchasing and performance of public procurement, a case of Rwanda Basic Education Board (REB). The specific objectives were to examine the relationship between cost management and performance of public procurement at REB, to establish the relationship between supplier relationship and performance of public procurement at REB, to establish the relationship between records management and performance of public procurement at REB and to examine the relationship between procurement plan management and performance of public procurement. A cross sectional data was collected from a sample of 112 staff from REB and its supplier/contractors in the period 2016-2018.  Data was collected using a close-ended questionnaire. The literature review was based on the institutional, network and agency theories. Empirical literature on variables studied in this study were also reviewed.The results on the first objective indicated a positive relationship between cost management and performance of public procurement at REB. For the second objective, the results indicated a positive relationship between supplier relationship and performance of public procurement at REB. For the third objective, the results indicated the positive relationship between records management and performance of public procurement at REB and for the fourth objective, the findings indicated a positive relationship between procurement plan management and performance of public procurement. Findings also revealed that among the predictors procurement plan management was noted to be a better predictor of relationship. The researcher recommends Government of Rwanda to give important place in public procurement items that were produced/ manufactured in Rwanda. Apart from enhancing made in Rwanda, the researcher recommends the government of Rwanda to review the public procurement process. The researcher recommends that trainings in procurement planning shall be offered to procurement officers and other people in connection with public procurement. For REB, the researcher recommends them to put in place strategic purchasing policy which shall determine why where, when and what services, works and goods to be purchased. The researcher also recommends REB to review the way archive for tender documents is maintained.